Cold-Adapted Glutathione S-Transferases from Antarctic Psychrophilic Bacterium Halomonas sp. ANT108: Heterologous Expression, Characterization, and Oxidative Resistance - Yanhua Hou; Chenhui Qiao; Yifan Wang; Yatong Wang; Xiulian Ren; Qifeng Wei; Quanfu Wang (Marine Drugs, 2019)
Glutathione S-transferases are one of the most important antioxidant enzymes to protect against oxidative damage induced by reactive oxygen species. In this study, a novel gst gene, designated as hsgst, was derived from Antarctic sea ice bacterium Halomonas sp. ANT108 and expressed in Escherichia coli (E. coli) BL21. The hsgst gene was 603 bp in length and encoded a protein of 200 amino acids. Compared with the mesophilic EcGST, homology modeling indicated HsGST had some structural characteristics of cold-adapted enzymes, such as higher frequency of glycine residues, lower frequency of proline and arginine residues, and reduced electrostatic interactions, which might be in relation to the high catalytic efficiency at low temperature. The recombinant HsGST (rHsGST) was purified to apparent homogeneity with Ni-affinity chromatography and its biochemical properties were investigated. The specific activity of the purified rHsGST was 254.20 nmol/min/mg. The optimum temperature and pH of enzyme were 25 °C and 7.5, respectively. Most importantly, rHsGST retained 41.67% of its maximal activity at 0 °C. 2.0 M NaCl and 0.2% H2O2 had no effect on the enzyme activity. Moreover, rHsGST exhibited its protective effects against oxidative stresses in E. coli cells. Due to its high catalytic efficiency and oxidative resistance at low temperature, rHsGST may be a potential candidate as antioxidant in low temperature health foods.